2015
DOI: 10.1186/s12885-015-1758-z
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and the risk of gastric cancer: a meta-analysis of prospective cohort studies

Abstract: BackgroundSeveral observational studies suggest that coffee consumption may be associated with an increased risk of gastric cancer, but the results are inconsistent. We conducted a meta-analysis to evaluate the relationship of coffee consumption with gastric cancer risk and quantify the dose–response relationship between them.MethodsRelevant prospective studies were identified by a search of PubMed, Embase, and Web of Science to May 2015 and by reviewing the references of retrieved articles. Two independent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Although some researchers have a negative view of the relationship between smoking and an increased risk of gastric cancer, 56 others have an affirmative view, 57,58 and the IARC refers to smoking as a carcinogen with sufficient evidence. Three meta‐analyses on the intake of coffee and risk of gastric cancer showed inconsistent results: one suggested that the intake of coffee is related to a decrease in the risk of gastric cancer, 59 another showed no correlation, 60 and the remaining one showed no correlation but suggested involvement in an increased risk of gastric cardiac cancer 61 . Similar results were obtained for the intake of green tea.…”
Section: [I] Risk Stratification Of Gastric Cancer Before Endoscopic mentioning
confidence: 81%
“…Although some researchers have a negative view of the relationship between smoking and an increased risk of gastric cancer, 56 others have an affirmative view, 57,58 and the IARC refers to smoking as a carcinogen with sufficient evidence. Three meta‐analyses on the intake of coffee and risk of gastric cancer showed inconsistent results: one suggested that the intake of coffee is related to a decrease in the risk of gastric cancer, 59 another showed no correlation, 60 and the remaining one showed no correlation but suggested involvement in an increased risk of gastric cardiac cancer 61 . Similar results were obtained for the intake of green tea.…”
Section: [I] Risk Stratification Of Gastric Cancer Before Endoscopic mentioning
confidence: 81%
“…Coffee is one of the most popular beverages worldwide and contains hundreds of biologically active phytochemicals, including many with antioxidant activity. Therefore, the relationships between coffee drinking and the incidence/mortality of cancer have been studied, especially in the gastrointestinal tract [ 10 ]. Thus, the potential role of coffee drinking in gastric cancer remains under study.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies clearly reported an exposure dose; thus the results can be interpreted only generically for high coffee intake compared with low intake or no consumption. The variation in effects by the dose of coffee or caffeine was evaluated in 25 nonoverlapping meta-analyses testing for linear association with 39 outcomes (8, 18, 21, 25, 28, 32, 34, 38, 39, 49, 55, 68, 69, 76-79, 83, 84, 104, 127, 134, 151, 153) (see Supplemental Figure 1) and 16 using a nonlinear dose-response meta-analysis of 24 outcomes (26,29,34,39,52,53,61,67,92,103,111,120,126,129,148,154) (Figure 4). Meta-analyses of liver (8), breast (69), endometrial (153), skin (melanoma) (78), colon (34), and prostate (151) cancers; all-cause mortality (49) and mortality from cardiovascular disease (CVD) (84); Parkinson's disease (25); depression; type-2 diabetes (28); cirrhosis (55); and chronic liver disease (8) reported significantly decreased risks for the incremental intake of coffee from 1 to 4 cups/day (depending on the study reference); and significantly decreased risks were also reported for endometrial cancer (153), Parkinson's disease (25), depression (39), atrial fibrillation (21), and type-2 diabetes (28) for incremental intake of 100 to 300 ml/day of caffeine (depending on the study reference) (Supplemental Figure 1).…”
Section: Wwwannualreviewsorg • Coffee and Human Health 137mentioning
confidence: 99%
“…In contrast, metaanalyses conducted for colorectal, colon and rectal cancers (33-35, 50, 65, 141); breast cancer (52,69,119,141); and pancreatic cancer (31,96,104,123,141) showed differences in the statistical significance of the effects, but not in the direction. Moreover, increments in statistical significance or changes in the direction of the association were found in meta-analyses of oral or laryngeal cancer (16,98,124), atrial fibrillation (caffeine exposure) (14,21), gastric cancer (3,27,67,76,112,135,136,143), bladder cancer (43,134,141,154), and Alzheimer's disease and cognitive disorders (caffeine exposure) (58, 79, 109) (Supplemental Table 1).…”
Section: Figurementioning
confidence: 99%